Abadaringi. Jeroen Janssen Oogachtend, Leuven, 2015 - Van Damme, Patrick (Afrika Focus, 2016)
Abadaringi is a so-called graphic novel that relates the dramatic events of the 1994 Rwandan genocide through the eyes of both the author and his former students. Before the events Janssen taught in an Arts School in Nyundo. He returned 20 years later to meet ceux de l’Ecole d’Art (which is the meaning of Abadaringi). Using his discussions with them he reconstructs an idiosyncratic history. His respondents do not accuse, they remain sympathetic and open. Janssen clearly does not want to tell us who was right or wrong. Rather, he tries to bring us back to the Rwanda he knew. What results is a (literally) colourful set of testimonies, set in, we might say, 50 shades of green. Don’t expect a profound analysis, but do appreciate his story-telling skills. And if it is the ‘truth’ you seek (which truth ? whose truth ?) then turn to serious non-fiction literature or documentaries . A ‘nice’ read in an unusual format !